Development of Interactive Comic Media with a Contextual Approach to Social Science Learning for Primary School - Indawati, Ninik; Sulistyowati, Prihatin; Andariana, Friorina Tri Puspa; Sari, Yuli Ifana; Fauzan, Fauzan (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This study aims to develop interactive comic media with a contextual approach for Social Science learning in grade 3 of elementary schools in Cluster 1, Tumpang District, using the Borg & Gall development model. This model involves ten stages, from research and data collection to product implementation and dissemination. The validity tests indicate high feasibility levels, with 94% from material experts, 74% from language experts, 90% from media experts, and 98% from teachers. Additionally, learning evaluation results show an average student score of 90, exceeding the minimum passing grade (KKM) of 70. These findings demonstrate that interactive comic media is effective for Social Science learning. Hence, this media serves as an innovative solution to improve the quality of Social Science education in elementary schools.